Further cleaning of the name pool in the New World Commelina (Commelinaceae), and notes on the African C. aquatica - Hassemer, Gustavo (Phytotaxa, 2020)
Study of the Commelina names published for the Americas and their original materials, in the context of a continental taxonomic revision of the genus, evidenced the need for typifications and synonymisations. In this work, 18 names are lectotypified (Athyrocarpus pseudomonosperma, C. aquatica, C. bravoa, C. diffusa var. cordispatha, C. dubia Redouté nom. illeg., C. erecta f. intercursa, C. formosa, C. glabra, C. nervosa, C. pallida, C. pallida var. parviflora, C. pilosula, C. quitensis var. mandonii, C. stricta, C. undulata Lodd. nom. illeg., C. virginica var. massonii, Nephralles parviflora and Phaeosphaerion efoveolaltum), one name neotypified (C. polygama), one name epitypified (C. longicaulis) and eight new synonymisations proposed. Evidence is presented that the African species C. aquatica, which is morphologically similar to the American C. longicaulis but has a different chromosome number, is most probably not conspecific with C. diffusa. Furthermore, the situation of seven Commelina names currently recognised in some sources, which however were never validly published, is discussed.